2023
DOI: 10.3390/jtaer18020042
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Blockchain Technology Adoption in the Tourism Industry from a Sustainability Perspective

Abstract: The deployment of Blockchain technology in the tourism industry is already becoming a reality with the gradual emergence of innovative business models. At its core is the promise of improving the efficiency of the tourism service value chain and enhancing the quality of the service provided to the end customer. This paper analyses research trends focused on using Blockchain technology in tourism. The aim is to determine how this technology impacts the tourism sector and its sustainability. A systematic review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…With the increasing of using BoT in tourism industry (Prados‐Castillo et al, 2023), several studies such as Lee et al (2021) and Suanpang et al (2021) have identified the potential benefits of BoT in enhancing the authenticity and trust of tourism services, while another study by Gao et al (2021) proposed a blockchain‐based system for managing tourism data and providing real‐time recommendations to tourists. Additionally, a study by Yu et al (2021) proposed a blockchain‐based system for improving the efficiency of tourism supply chains, while a study by Nambiar et al (2021) explored the potential of BoT in enhancing the safety and security of tourists.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…With the increasing of using BoT in tourism industry (Prados‐Castillo et al, 2023), several studies such as Lee et al (2021) and Suanpang et al (2021) have identified the potential benefits of BoT in enhancing the authenticity and trust of tourism services, while another study by Gao et al (2021) proposed a blockchain‐based system for managing tourism data and providing real‐time recommendations to tourists. Additionally, a study by Yu et al (2021) proposed a blockchain‐based system for improving the efficiency of tourism supply chains, while a study by Nambiar et al (2021) explored the potential of BoT in enhancing the safety and security of tourists.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a study by Kim et al (2021) proposed a BoT‐based system for managing tourist information and improving the accessibility of tourism services. Thus, the integration of BoT has the potential to revolutionize the tourism industry by enabling the creation of new and innovative tourism experiences, enhancing operational efficiency, and improving the security of data and transactions (Kim et al, 2019; Prados‐Castillo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature review Innovation is derived from the Latin word "innovatio", it is the process of creating, implementing, or renewing a new idea, processes, products, and services (Feng et al, 2020;Grissemann et al, 2013;Hjalager, 2010). From an economic perspective it adds value, increases sales and improves financial performance (Booyens and Rogerson, 2016), is linked to the growth of economies (Pikkemaat and Zehrer, 2016;Prados-Castillo et al, 2023;Puertas et al, 2022), allows to improve technology, create wealth and develop sustainable competitive advantages (Anning-Dorson, 2017;Lelo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%